Proposta de modelo para indicador de eficiência em redes de cooperação horizontal utilizando o índice de Malmquist - Costa, Ercules (2017)
In the present study, a model is proposed to measure the efficiency of the companies that participate in the Horizontal Cooperation Networks (RCH), using the Data Envelopment Analysis (DEA) technique and admitting variable returns of scale to calculate the Malmquist index. A literature search pointed to the lack of quantitative studies that prove the competitive advantages of the companies that cooperate in the network. This motivated the development of the method that was applied in a RCH hotel located in Ilha do Mel, southern Brazil. Data on inputs and outputs were collected over a period of five years (2011 to 2015), in fifteen companies, with five participants and ten non-participants in the network. The analysis of the results showed that after the founding of the network, some participating companies took a year to become reference benchmarks. Although the study indicates a decrease in productivity for all decision-making units (DMU), the decomposition of the Malmquist index revealed efficiency gains in the companies participating in the network, confirming statistically the hypothesis raised. In addition to contributing to the construction of the quantification model, this study can be used as a comparison method, helping the governance to identify DMU with difficulties and to elaborate practices for better maintenance of the network.